2017
DOI: 10.1016/j.cell.2017.06.016
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ-Dependent Tissue-Immune Homeostasis Is Co-opted in the Tumor Microenvironment

Abstract: Summary Homeostatic programs balance immune protection and self-tolerance. Such mechanisms likely impact autoimmunity and tumor formation, respectively. How homeostasis is maintained and impacts tumor surveillance is unknown. Here, we find that different immune mononuclear phagocytes share a conserved steady-state program during differentiation and entry into healthy tissue. IFNγ is necessary and sufficient to induce this program, revealing a key instructive role. Remarkably, homeostatic and IFNγ-dependent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 52 publications
5
128
0
Order By: Relevance
“…In accordance with the increased immunosuppressive landscape in melanoma, our study identified increased DCs expressing suppressive markers that have previously been associated with tolerogenic, immunoregulatory function. Similar to SOCS2, which was previously identified as a protein expressed by dendritic cells that is critical for limiting antitumor immune response in MM, SOCS3 is also a member of the suppressor of cytokine signalling (SOCS) proteins family. SOCS3 expression by dendritic cells has not previously been described in human melanoma.…”
Section: Discussionmentioning
confidence: 93%
“…In accordance with the increased immunosuppressive landscape in melanoma, our study identified increased DCs expressing suppressive markers that have previously been associated with tolerogenic, immunoregulatory function. Similar to SOCS2, which was previously identified as a protein expressed by dendritic cells that is critical for limiting antitumor immune response in MM, SOCS3 is also a member of the suppressor of cytokine signalling (SOCS) proteins family. SOCS3 expression by dendritic cells has not previously been described in human melanoma.…”
Section: Discussionmentioning
confidence: 93%
“…The role of IFN‐γ in maintaining immune homeostasis is less well described. A recent study suggests that IFN‐γ regulates homeostasis in healthy tissue by upregulation of suppressor‐of‐cytokine‐2 (SOCS2) protein expressed by tissue phagocytes . Moreover, we previously described that IFN‐γ induces indoleamine 2, 3‐dioxygenase production from gingival fibroblast cells .…”
Section: Discussionmentioning
confidence: 95%
“…IFNγ could induce expression of suppressor‐of‐cytokine‐2 (SOCS2) protein, a conserved program transcript, which is expressed by mononuclear phagocytes infiltrating primary melanoma. SOCS2 limits adaptive antitumor immunity and DC‐based priming of T cells in vivo . These results link immune homeostasis to key determinants of antitumor immunity and escape, uncovering the underlying mechanism by which IFNγ contributes to tumor escape in the tumor microenvironments.…”
Section: The Role Of Ifnγ In Tumor Escapementioning
confidence: 92%